A Space‐Charge Treatment of the Increased Concentration of Reactive Species at the Surface of a Ceria Solid Solution. Issue 46 (12th October 2017) - Zurhelle, Alexander F.; Tong, Xiaorui; Klein, Andreas; Mebane, David S.; De Souza, Roger A.
Abstract: A space‐charge theory applicable to concentrated solid solutions (Poisson–Cahn theory) was applied to describe quantitatively as a function of temperature and oxygen partial pressure published data obtained by in situ X‐ray photoelectron spectroscopy (XPS) for the concentration of Ce 3+ (the reactive species) at the surface of the oxide catalyst Ce0.8 Sm0.2 O1.9 . In contrast to previous theoretical treatments, these calculations clearly indicate that the surface is positively charged and compensated by an attendant negative space‐charge zone. The high space‐charge potential that develops at the surface (>0.8 V) is demonstrated to be hardly detectable by XPS measurements because of the short extent of the space‐charge layer. This approach emphasizes the need to take into account defect interactions and to allow deviations from local charge neutrality when considering the surfaces of oxide catalysts. Abstract : A Poisson–Cahn treatment explains the experimentally observed complex behaviour of [Ce 3+ ] at the surface of the ceria‐based catalyst, Ce0.8 Sm0.2 O1.9 . Even at the surface of such a highly concentrated solid solution, local charge neutrality is found to be violated, with the formation of a positively charged surface and an extended negative space‐charge zone.